ANALISIS KETIDAKKONDUSIFAN KELAS PADA PEMBELAJARAN MATEMATIKA BERBASIS PERMAINAN DI SEKOLAH DASAR DALAM PERSPEKTIF JOYFUL LEARNING - Nur Azizah, Lutfi; Sutrisno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the causes and forms of classroom disruption that emerged during a game-based mathematics lesson for second-grade students at SDN Geneng 02, and to examine the extent to which the practice reflects the principles of joyful learning. A qualitative descriptive case-study approach was employed, with data collected through structured observation of one classroom teacher and twenty second-grade students during a lesson on counting, reading, and writing numbers 51-100. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the use of concrete media (straws and a number board) combined with a game-based worksheet ("math battle") successfully increased student enthusiasm, participation, and self-confidence. However, the high level of enthusiasm also produced a noisy and less orderly classroom atmosphere, partly because the teacher did not conduct an ice-breaking transition after the worksheet activity and skipped the group presentation stage. These omissions weakened opportunities for emotional regulation and reinforcement of understanding. The study concludes that joyful learning in mathematics instruction is not merely about generating excitement through games, but requires a deliberate balance between engagement and structured classroom management, including transitional activities such as ice breaking, to sustain a conducive and meaningful learning environment.